2014
DOI: 10.1002/anie.201402000
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Profiling of Glutathione S‐transferase with Engineered Enzymes and Matched Glutathione Analogues

Abstract: The identification of specific substrates of glutathione S-transferases (GSTs) is important for understanding drug metabolism. A method termed bioorthogonal identification of GST substrates (BIGS) was developed, in which a reduced glutathione (GSH) analogue was developed for recognition by a rationally engineered GST to label the substrates of the corresponding native GST. A K44G-W40A-R41A mutant (GST-KWR) of the mu-class glutathione S-transferases GSTM1 was shown to be active with a clickable GSH analogue (GS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Imaging tools capable of detecting endogenous protein S -glutathionylation (PSSG) from live mammalian cells have drawn significant interests in recent years. When cells are under oxidative stress, PSSG occurs, whereby cysteines in affected proteins form disulfide bonds with endogenous GSH resulting in the formation of glutathionylated proteins (protein-SSG) (Figure a). This process is catalyzed by redox enzymes together with reactive oxygen species (ROS) and is closely associated with the progression of many diseases .…”
Section: Resultsmentioning
confidence: 99%
“…Imaging tools capable of detecting endogenous protein S -glutathionylation (PSSG) from live mammalian cells have drawn significant interests in recent years. When cells are under oxidative stress, PSSG occurs, whereby cysteines in affected proteins form disulfide bonds with endogenous GSH resulting in the formation of glutathionylated proteins (protein-SSG) (Figure a). This process is catalyzed by redox enzymes together with reactive oxygen species (ROS) and is closely associated with the progression of many diseases .…”
Section: Resultsmentioning
confidence: 99%
“…It not only can conjugate with biotin for purification in proteomics but also can click with fluorophores for imaging applications. Also, azido-glutathione may be used to identify small molecule substrates of glutathione S-transferase, as shown in a recent report . Such efforts could significantly contribute to an enhanced understanding of the roles of glutathione and glutathionylation in redox regulation.…”
mentioning
confidence: 96%
“…Also, azido-glutathione may be used to identify small molecule substrates of glutathione S-transferase, as shown in a recent report. 21 Such efforts could significantly contribute to an enhanced understanding of the roles of glutathione and glutathionylation in redox regulation. Journal of the American Chemical Society…”
mentioning
confidence: 99%
“…Contributing to the recent effort toward substrate profiling for a wide range of transferases, Deng and colleagues formulated a technique called 'bioorthogonal identification of GST substrates' (BIGS) by developing allele-specific pair of GST mutant and modified reduced glutathione. 117 Upon analysis of the crystal structure of GSTM1 from S. japonicum, they generated a K44G/W40A/ R41A triple mutant (GST-KWR) that was able to modify a homopropargylic ester of GSH (GSH-R1) as its substrate with efficiency comparable to the wild-type GSTM1-GSH pair ( Figure 9C). Although the mutant was still active toward GSH, it showed preference toward modified GSH in a competitive assay, demonstrating its functional orthogonality.…”
Section: Acs Chemical Biologymentioning
confidence: 99%
“…As an interesting application, the GST-KWR and GSH-R1 pair was used to identify multiple substrates, such as cyclodopaglucoside and callystatin A, from the Chinese herbal medicine Ganmaochongli using LC-MS/MS of the enriched sample ( Figure 9C). 117 Recently, Ahn and colleagues have demonstrated that hole-bearing glutathione synthetase can synthesize a GSH analogue containing bumped azido-alanine, providing a ACS Chemical Biology Reviews dx.doi.org/10.1021/cb500651d | ACS Chem. Biol.…”
Section: Acs Chemical Biologymentioning
confidence: 99%